Notification of completion rectification / Ahmad Hassanuddin Md Ishak - Ahmad Hassanuddin, Md Ishak (2019)
The task been given is to perform a defect inspection mainly for project Suriaman 2A at Bandar Sri Sendayan, in this case study is Unit 188. The doublestorey terrace has 277 units in total. Besides, Suriaman 2A is neighboring with Suriaman 2B and Suriaman 1. The units in Suriaman 2A were built-up of 2,807 square feet and two-storey super link comes with 4 bedrooms and bathrooms each. This project was constructed in 2015 and completed in 2018. The project team involved are KW ASSOCIATE ARCHITECTS SDN BHD Architect, MEXCELCON is the main contractor for the project and also act as the engineering team. The sub-contractor for electrical is OTT Electrical. Mr. Desmond Siaw is the Project Unit Leader (PUL) the one who responsible to coordinate and lead the team on site.